2011
DOI: 10.1645/ge-2687.1
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Neospora caninum in Dairy Buffaloes in Lahore District, Pakistan

Abstract: Seroprevalence of Neospora caninum in dairy buffaloes ( Bubalus bubalis ) was assessed in the Lahore District of Punjab Province, Pakistan. The study revealed an overall prevalence of 54.7% for N. caninum antibodies determined through a competitive enzyme-linked immunosorbent assay performed on randomly collected serum samples. The highest prevalence was observed in buffaloes >3-5 yr of age (64.1%), followed by 57.9% for 5 to 6 yr olds, and 55.8% in 1-yr-old neonates, with high probability of infection under i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 21 publications
5
36
0
Order By: Relevance
“…N. caninum has been identified in wild canids and dingo in Australia [3,6], and, world-wide in many wild ruminant species, including water buffalo (Bubalus bubalis) [7]. Water buffalo have tested positive for N. caninum in multiple countries of Asia [8][9][10][11][12], Europe [13], South America [14,15] and Africa [16]. From the worldwide literature it would appear that water buffalo generally show a higher seroprevalence than domestic cattle [2].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…N. caninum has been identified in wild canids and dingo in Australia [3,6], and, world-wide in many wild ruminant species, including water buffalo (Bubalus bubalis) [7]. Water buffalo have tested positive for N. caninum in multiple countries of Asia [8][9][10][11][12], Europe [13], South America [14,15] and Africa [16]. From the worldwide literature it would appear that water buffalo generally show a higher seroprevalence than domestic cattle [2].…”
mentioning
confidence: 99%
“…These buffalo had a higher calving and weaning rate than the co-habiting domestic cattle, despite a higher seroprevalence for N. caninum. Only few studies, have, thus far, shown links between naturally acquired N. caninum infection and abortion in B. bubalis [8,13], although experimentally abortion can be induced readily [17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Neospora caninum, the etiological agent of bovine neosporosis, is an abortifacient protozoan parasite, implicated in causing infection and subsequent reproductive losses in cattle (2), water buffaloes (3) and other domestic (4) as well as wild animal species (5). Neosporosis in buffalo has been documented from several regions of the world, such as from Brazil (6), Egypt (7), and Thailand (8), and also from Pakistan (9). Economic losses instigated by N. caninum worldwide can be demonstrated as direct costs mediated by abortion (10), together with culling infected animals (11).…”
mentioning
confidence: 99%
“…Lesions caused by N. caninum in water buffaloes are uncommon, due to few studies showing direct association between the parasite and abortions [197,218,219]. The lesions seen naturally aborted buffalo caused by N. caninum consists of non-suppurative inflammation in placenta, brain, heart and other organs [33].…”
Section: Neosporosismentioning
confidence: 99%